Neurobehavioral Effects of Cephalosporins: Assessment of Locomotors Activity, Motor and Sensory Development in Zebrafish - Han, Ying; Zheng, Yangmin; Zhang, Jingpu; Hu, Changqin (Frontiers in Pharmacology, 2018)
Most third- and fourth-generation cephalosporins, such as cefotaxime (CTX), cefmenoxime (CMX), cefepime (CPM), and cefpirome (CPO), contain an aminothiazoyl ring at the C-7 position. Drug impurity, which may be produced either during synthesis or upon degradation, can induce adverse effects. Various reports have indicated that neurotoxicity is a side effect of cephalosporin. In this study, we developed methods for assessing the free-swimming activities and behaviors in zebrafish larvae in response to continuous darkness and stimulation of light-to-dark photoperiod transition by chemical treatments. We also performed transcriptome analysis to identify differentially expressed genes (DEGs). Gene ontology analysis revealed that various processes related to nervous system development were significantly enriched by DEGs. We integrated 16 DEGs with protein–protein interaction networks and identified neuroactive ligand–receptor interaction (e.g., GABA and GRM1A) pathway was regulated by the compounds. Our findings suggested that neurobehavioral effects mainly depends on the mother nucleus structure 7-aminocephalosporanic acid (7-ACA) and the substitution at the C-3 position. In addition, gad2, or111-4, or126-3, grm1a, opn8c, or111-5, or113-2 and or118-3 may potentially be utilized as novel biomarkers for this class of cephalosporins, which causes neurotoxicity. This study provides neurological behavior, transcriptome, and docking information that could be used in further investigations of the structures and developmental neurotoxicity relationship of chemicals.